Sex‐specific differences in chronic thromboembolic pulmonary hypertension. Results from the European CTEPH registry. (24th September 2019) - Barco, Stefano; Klok, Frederikus A.; Konstantinides, Stavros V.; Dartevelle, Philippe; Fadel, Elie; Jenkins, David; Kim, Nick H.; Madani, Michael; Matsubara, Hiromi; Mayer, Eckhard; Pepke‐Zaba, Joanna; Simonneau, Gérald; et al.
Abstract: Background: Women are more susceptible than men to several forms of pulmonary hypertension, but have better survival. Sparse data are available on chronic thromboembolic pulmonary hypertension (CTEPH). Methods: We investigated sex‐specific differences in the clinical presentation of CTEPH, performance of pulmonary endarterectomy (PEA), and survival. Results: Women constituted one‐half of the study population of the European CTEPH registry (N = 679) and were characterized by a lower prevalence of some cardiovascular risk factors, including prior acute coronary syndrome, smoking habit, and chronic obstructive pulmonary disease, but more prevalent obesity, cancer, and thyroid diseases. The median age was 62 (interquartile ratio, 50‐73) years in women and 63 (interquartile ratio, 53‐70) in men. Women underwent PEA less often than men (54% vs 65%), especially at low‐volume centers (48% vs 61%), and were exposed to fewer additional cardiac procedures, notably coronary artery bypass graft surgery (0.5% vs 9.5%). The prevalence of specific reasons for not being operated, including patient′s refusal and the proportion of proximal vs distal lesions, did not differ between sexes. A total of 57 (17.0%) deaths in women and 70 (20.7%) in men were recorded over long‐term follow‐up. Female sex was positively associated with long‐term survival (adjusted hazard ratio, 0.66; 95% confidence interval, 0.46‐0.94). Short‐term mortality was identical in the two groups. Conclusions: Women with CTEPH underwent PEA less frequently than men, especially at low‐volume centers. Furthermore, they had a lower prevalence of cardiovascular risk factors and were less often exposed to additional cardiac surgery procedures. Women had better long‐term survival.